Teacher Participation in School Academic Administration of Tap Tao Educational Network Center 2 under Chiang Rai Primary Educational Service Area Office 4 - Rattanadechasakul, Sittipong; Mulkhien, Sitthichai (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
This research aimed to study the conditions and developing methods of teacher participation on academic administration of Tap Tao Educational Network Center 2, under Chiang Rai Primary Educational Service Area Office 4. Informants were 78 administrators and teachers. Research tools were questionnaire and interview. Data were analyzed using frequency, percentage, average, standard deviation and content analysis. The results showed that overall condition of teacher participation were at high level considering each aspect in descending order namely the development of learning process (μ=3.88); internal quality assurance systems and educational standards (μ==3.73); teaching and learning management in educational institutions (μ=3.67); and development and promotion of learning resources (μ=3.67) respectively. Development guidelines are that educational institutions should have a budget for producing teaching and learning materials; always develop innovative media and technology; continuously promote the creation and development of learning resources; and develop an internal quality assurance system with a development plan. Also a committee to operate and use the evaluation results to develop the internal insurance system shoud be set up.